Boron nitride (BN) and BN based multiple-layer interphase for SiCf/SiC composites: A review. Issue 23 (1st December 2022) - Chen, Maolin; Pan, Ling; Xia, Xiaodong; Zhou, Wei; Li, Yang
Abstract: The interphase in continuous SiC fiber reinforced SiC ceramic matrix composites (SiCf /SiC) generally plays a key role for load-transfer, interfacial debonding and fibers protection, consequently tailoring the mechanical properties, thermodynamic stability, corrosion resistance of composites. Hexagonal boron nitride (h-BN), which possesses a graphite-like layered structure and better oxidation resistance compared with pyrolytic carbon (PyC), is now considered as one of the best candidates as interphase in SiCf /SiC composites. In this paper, the influences of different preparation methods on the microstructure, crystal structure, and thickness of boron nitride (BN) interphase are summarized. And the research progress of CVI (or CVD) preparation of BN and BN-based multiple-layers interphases are emphasized. The effects of different preparation methods on the mechanical and thermal properties of SiCf /SiC composites and the solutions to improve the crystal ordering of BN are summarized. Moreover, the future development regarding optimization in the preparation method and microstructure tailoring of BN interphase are discussed.